SYNERGISTIC EFFECT OF ANTIBIOTIC WITH GREEN SYNTHESIZED SILVER NANO PARTICLES AGIANST UROPATHOGENIC E.COLI BIOFILM - Muna H. M.; N. S. Alshaikhly; M. H. M Al-khafaji (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The bacterial ability to form biofilm had been complicated the infection healing process, due to antibiotic resistance. Urinary tract infection is an optimal example of such infections that caused by bacterial biofilms. So the current study aimed to find an alternative method to inhibit the uropathogenic bacteria using nanotechnology. Uropathogenic Escherichia coli (UPEC) was isolated from 110 clinical samples. These bacterial isolated were tested for their ability to form biofilm by two methods: Microtiter plate and congo red agar. Antibiotic susceptibility was detected to determine the multidrug-resistant isolates. An ecofriendly green method was depended for the synthesis of silver nanoparticles (AgNPs) using alcoholic extract of Lepidium meyenii yellow root. Silver nanoparticles were characterized by several techniques, and it was detected with a diameter of 44.89 nm. Anti-biofilm activity of AgNPs alone and with antibiotic was detected and the Scanning electron microscopy observations clearly indicated that 7.1825 mg/ml AgNPs prevented the biofilm formation. This is the first worldwide evidence-based research study about the biosynthesis of silver nanoparticles from alcoholic yellow root extract of plant Lepidium meyenii and use it against UPEC biofilm.